2022
DOI: 10.3390/cancers14071851
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR Signaling Modulates in Mesenchymal Stem Cells the Expression of miRNAs Involved in the Interaction with Breast Cancer Cells

Abstract: We previously demonstrated that the epidermal growth factor receptor (EGFR) modulates in mesenchymal stem cells (MSCs) the expression of a number of genes coding for secreted proteins that promote breast cancer progression. However, the role of the EGFR in modulating in MSCs the expression of miRNAs potentially involved in the progression of breast cancer remains largely unexplored. Following small RNA-sequencing, we identified 36 miRNAs differentially expressed between MSCs untreated or treated with the EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The interpretation of those caveats is not clear. Nevertheless, the suggested miRNAs-23c and -4328 have been scientifically studied and suggested to be of functional relevance in cancer [23,[53][54][55][56][57][58][59]. The tissue localization of the miRNA-23c and -4328 will need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of those caveats is not clear. Nevertheless, the suggested miRNAs-23c and -4328 have been scientifically studied and suggested to be of functional relevance in cancer [23,[53][54][55][56][57][58][59]. The tissue localization of the miRNA-23c and -4328 will need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how cMo-1s regulate adipogenesis and identify tractable therapeutic targets, the ligand-receptor analysis was performed, which demonstrated that cMo-1s might promote proinflammatory and pro-adipogenic mediator expression in MSC1-S1s (Supplementary Data 20). Correspondingly, cMo-1s expressed higher levels of epidermal growth factor receptor ligands known to regulate MSC activation 26 . Interestingly, the results suggested that both cMo-1s and MSC1-S1s in CF were major producers of adipokines and cytokines such as IL-6, but the IL-6 receptor differed in these subsets (IL-6R and HRH1, respectively) (Fig.…”
Section: Pro-inflammatory Monocyte Subset Accumulates In Cf and Promo...mentioning
confidence: 99%
“…In particular, the hsa-miR-122-5p has been identified in liquid biopsies of BC patients, especially in more aggressive subtypes and models [76,144,196,197]. Interestingly, Gallo et al (2022) demonstrated that mesenchymal stem cells (MSCs) export hsa-miR-23c which seems to control the growth of TNBC cells [198]. Although the hypothesis that MSCs express hsa-miR-23c and this miRNA can reach the bloodstream is valid, it is somewhat difficult to define whether the miRNA present in plasma comes from MSCs or tumor cells, complicating diagnostic approaches of this putative biomarker.…”
Section: Relevant Cf-mirna Regions In Tnbc Patientsmentioning
confidence: 99%
“…(2022) described a mechanism to induce a cross-talk between Mesenchymal Stem Cells (MSCs) and TNBC cells [198]. Then, it was proven that hsa-miR-513a-5p can inhibit the expression of progesterone receptors in BC tissues [374].…”
Section: Relevant Vesicular Mirna Regions In Luminal Bc Patientsmentioning
confidence: 99%